Gender Transversality and Social Politics in the Budget of Mato Grosso State - Rosângela Saldanha Pereira; Xavier Rambla; Kamila Paceluika Silva; Cássia Daiane Ciriaco (Revista Estudos Feministas, 2010)
The incorporation of the perspective of gender in the public policies in Brazil is quite recent, being few the registry and analysis of the provincial and municipal experiences, in special, that concern the initiatives of formulation and management of public budgets. This article tries to contribute to the overcoming of this fault, discussing and analyzing the 2004-2007 Pluriannual Plan of the Government of Mato Grosso State, under the light of the transforming approach (Sen, 1998) and of the feminist theory. Another discussion is whether the government is incorporating the political commitment assumed by the federal government to face the gender inequalities and to make the cross-sectional management of its public policies, specified in the National Plan of Policies for the Women